Application of emerging technologies to fruits processing with high nutritional quality. – A review - Gamboa Santos, Juliana; Rodríguez, Johanna; Carvajal, Gabriela; Pilamala, Araceli (Revista Colombiana de Investigaciones Agroindustriales, 2016)
The worldwide development in fruits processing, due to improved preservation techniques, transportation, marketing, and distribution systems, can offer to consumers a wide range of healthy foods increasingly demanded. However, most of the constituents of interest in foodstuffs are temperature sensitive and vulnerable to chemical, physical and microbiological changes. Conventional processes applied in the food industry provide losses of nutritive and bioactive compounds while consuming high levels of energy, time and water. In response to thes disadvantages, in recent years a large number of alternative technologies that enable the processing at low or mild temperatures emerged as potential treatments to inactivate enzymes and microorganisms with minimum adverse effects on the food quality parameters. Studies who focus on the fruit processing allow to obtain comprehensive information about the behavior of these materials during different treatments, to contribute to the development of quality food, safe and healthy to maintain, as long as possible, the nutritional and organoleptic characteristic of fresh products. Para citar este artículo Gamboa-Santos, J., Rodríguez, J., Carvajal, G. y Pilamala, A. (2016). Aplicación de tecnologías emergentes al procesamiento de frutas con elevada calidad nutricional. – Una revisión. Rev. Colomb. Investig. Agroindustriales, 3(1), 57-75. DOI: http://dx.doi.org/10.23850/24220582.361